Methodology of Improving Independent Learning Skills of Future Fine Art Teachers (On the Example of Still Life in Colorful Paintings) - Khusan Kholmuratovich, Muratov; Sardor Mardanaqulovich, Abdulkhamidov; Rustam Ravshanovich, Jabbarov; Ugiloy Sharifovna, Khudaynazarova; Oykaram Shodiyevna, Baymurzayeva (International Journal of Psychosocial Rehabilitation, 2020)
Formation of the skills of independent learning in the system of creative preparation of students to gain deep knowledge and skills in the subjects of study plays a great role. One of the important conditions for the organization of the educational process in the preparation of specialists in accordance with modern requirements is the activation of independent educational activities of students. Self-education is the content of such qualities as independence, creativity, enterprise, and activeness of a specialist.